Factors affecting gene expression associated with the skin color of black-bone chicken in Thailand - Panuwat Khumpeerawat (Poultry Science, 2021)
ABSTRACT: The objective of this study was to investigate the effect of breed, sex, and age on the gene expression level of melanocortin 1 receptor (MC1R), DOPA chrome tautomerase (DCT), tyrosinase-related protein 1 (TYRP1), tyrosinase (TYR), and agouti signaling protein (ASIP) genes in Thai commercial chicken lines. All chicken have received Newscastle vaccination, and no antibiotics or any drugs were used in this study. Four chicken breeds including Black-Chinese, KU-Phuparn, Sri Mok, and Pradu Hang Dam were used in this study. These breeds can be classified by their skin color into 3 group including black (Black Chinese and KU-Phuparn), light black (Sri Mok), and yellowish white (Pradu Hang Dam). One hundred chickens per breed were used in this study. Breast skin tissue was randomly collected from 8 chickens (4 males, 4 females) per breed at 4, 8, 12, and 16 wk of age. The mRNA expression was analyzed using qRT-PCR and the gene expression level was calculated as 2−ΔΔCT. From the results, breed significantly (P < 0.01) affected the expression level for the 5 genes evaluated. Birds with the black skin color had greater TYRP1 and TYR gene expression when compared to chickens with light black and yellowish-white skin color, respectively. Whereas, chickens with yellowish-white skin color had greater ASIP gene expression when compared to chickens having the other skin colors. Sex significantly affected DCT, TYRP1, and TYR gene expression where the gene expression in males was greater when compared to females (P < 0.05). Age affected all gene expression levels (P < 0.01). At 4 wk of age, MC1R, DCT, TYRP1, and TYR gene expression was the highest and decreased as bird age increased (P < 0.05); however, ASIP gene expression was greatest at 8 wk of age. After 8 wk of age all gene expression for the genes evaluated in this study decreased as age increased. In addition, an interaction between breed and sex (P < 0.05) impacted DCT and ASIP gene expression. The results from this study showed that all genes evaluated can be used as candidate markers to further improve the blackness of the chicken's skin because the most desired skin color is black in the Thai black-bone chicken population.